2017
DOI: 10.1111/jam.13610
|View full text |Cite
|
Sign up to set email alerts
|

Detection of latent infections caused by Colletotrichum sp. in olive fruit

Abstract: This study is relevant because we set up a viable, non-hazardous alternative to paraquat to detect latent infections of Colletotrichum sp. using NaOH. The use of NaOH is a simple and eco-friendly tool that allows the determination of the level of latent infections by Colletotrichum in olives. Therefore, our method will be useful in decision-making processes for disease management before the appearance of the first visible symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
0
4
0
2
Order By: Relevance
“…In Greece, although the disease is known since 1920, its precise etiology only recently was elucidated, suggesting that the C. acutatum species complex is the predominant disease agent [ 20 ]. The most destructive disease symptoms occur most often on mature fruit in the form of brown-dark sunken rotten lesions that under moist conditions are covered by orange conidium masses [ 21 ]. Infected fruit are mummified and either drop onto the ground or remain attached on the trees, providing inoculum for primary latent infections that will occur during the spring on olive inflorescences [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Greece, although the disease is known since 1920, its precise etiology only recently was elucidated, suggesting that the C. acutatum species complex is the predominant disease agent [ 20 ]. The most destructive disease symptoms occur most often on mature fruit in the form of brown-dark sunken rotten lesions that under moist conditions are covered by orange conidium masses [ 21 ]. Infected fruit are mummified and either drop onto the ground or remain attached on the trees, providing inoculum for primary latent infections that will occur during the spring on olive inflorescences [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The most destructive disease symptoms occur most often on mature fruit in the form of brown-dark sunken rotten lesions that under moist conditions are covered by orange conidium masses [ 21 ]. Infected fruit are mummified and either drop onto the ground or remain attached on the trees, providing inoculum for primary latent infections that will occur during the spring on olive inflorescences [ 21 , 22 ]. In addition to mature fruit rot, leaf wilting and branch dieback may appear as a consequence of toxins production by the pathogen [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…to different strawberry varieties was relatively weak than that on wounded conditions ( Jayawardena et al, 2016 ). This may occur because of the inefficient penetration of pathogens on the non-wounded plant cell wall ( Than et al, 2008 ; Romero et al, 2018 ). Estrada et al (2000) found that temperature and humidity can affect the pathogenicity, conidial germination, and appressoria formation of Colletotrichum spp., which raised our interests in further studying the impacts of temperature and humidity on the infection of Colletotrichum spp.…”
Section: Discussionmentioning
confidence: 99%
“…La quiescencia puede deberse a varios factores: (i) diferencias nutricionales entre el fruto inmaduro y el fruto maduro con respecto al desarrollo del hongo; (ii) cambios metabólicos asociados con la maduración y alteraciones en el patrón de respiración del fruto; (iii) deficiencia en el hongo de enzimas pectinolíticas para invadir frutos inmaduros, (iv) presencia de compuestos tóxicos en frutos inmaduros que no se encuentran en frutos maduros (Adikaram et al, 2015). Romero et al (2017), sostienen que la detección de infecciones latentes en frutos de olivo (Olea europaea subsp. europaea L.) es útil para la toma de decisiones en el manejo de la enfermedad antes de la aparición de los primeros síntomas.…”
Section: Guédez Y Rodríguezunclassified
“…between the immature fruit and the mature fruit with respect to the development of the fungus; (ii) metabolic changes associated with ripening and alterations in the respiration pattern of the fruit; (iii) deficiency in the fungus of pectinolytic enzymes to invade immature fruits, (iv) presence of toxic compounds in immature fruits that are not found in mature fruits (Adikaram et al, 2015). Romero et al (2017), argue that the detection of latent infections in olive fruits (Olea europaea subsp. europaea L.) is useful for making decisions in the management of the disease before the appearance of the first symptoms.…”
Section: Guédez Y Rodríguezmentioning
confidence: 99%